2016
DOI: 10.1007/s10518-016-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Ground motion prediction in Beirut: a multi-step procedure coupling empirical Green’s functions, ground motion prediction equations and instrumental transfer functions

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This value for m b can be related to seismic yield in kt TNT equivalent of the explosion. According to Brax et al (2016) 37 the geological unit at the explosion site is comprised out of dolomite rocks and the region can be classified as International Building Code (IBC) class C (very dense soil and soft rock). Under these geological assumptions we use m b yield relations for wet hard rock 34 and for dry unconsolidated rock 7 to estimate a range of explosive yield of the explosions.…”
Section: Explosion Source Inversionmentioning
confidence: 99%
“…This value for m b can be related to seismic yield in kt TNT equivalent of the explosion. According to Brax et al (2016) 37 the geological unit at the explosion site is comprised out of dolomite rocks and the region can be classified as International Building Code (IBC) class C (very dense soil and soft rock). Under these geological assumptions we use m b yield relations for wet hard rock 34 and for dry unconsolidated rock 7 to estimate a range of explosive yield of the explosions.…”
Section: Explosion Source Inversionmentioning
confidence: 99%
“…In contrast, when deriving the SCEs and reducing them in Sections 5-7, reference only to IBC and EC8 will be given. The motivations of this choice are: (i) IBC is currently the reference code for the seismic design in USA, where UBC is not mandatory anymore; (ii) PS92 is an obsolete code in France, where EC8 is presently the reference code for the seismic design; (iii) EC8 is expected to be the only code which the Lebanese seismic design will be based on in the near future; (iv) almost all the Lebanese engineering schools refer to IBC and/or to EC8; (v) reference to IBC and EC8 is also typically used in the literature when dealing with Lebanese seismic design [19,20,37].…”
Section: Design Response Spectra For Lebanonmentioning
confidence: 99%
“…Many studies dealt with this matter, see e.g., [13][14][15][16][17][18], and most codes provide rules and suggestions for this purpose. A recent paper proposed a site-specific estimation of strong ground motions in the Lebanese area [19], and also showed that the Lebanese norm may give unsafe amplification factors for short period structures. In [20], a probabilistic study of the Lebanese seismic hazard was performed to provide design requirements.…”
Section: Introductionmentioning
confidence: 99%